GRADED CONTRACTION ON PAULI GRADING SL(3;C) - Saputra, Reynald
Lie algebra sl(n;C) is one of classical Lie algebra. In this research, we will see another Lie algebra that generated from grading contraction of the classical Lie algebra sl(n;C). The Lie algebra obtained is called the solution of the grading contraction. In particular, we will use Pauli grading (one of the fine grading for sl(n;C)) and review when n = 3. From the Pauli grading of sl(3;C), we will get 48 contraction equations and use the symmetry group of Pauli grading to solve it. Furthemore, we will also review when n = 2, n = 4 and the Levi decomposition of contraction Pauli grading sl(3;C).